The rule of law in the perspective of the principle of maintaining and deepening communication between people - Rossmanith, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The article deals with the issue of the rule of law in a broader and narrower sense, with reference to L.L. Fuller’s concept of the morality of law. The article also raises the question of the connection between formal requirements of the rule of law and the principle of maintaining and deepening communication between people.